Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if (4cos^2(9)-3)(4cos^2(27)-3)=tan K then K is equal to

if (4cos^2(9)-3)(4cos^2(27)-3)=tan K then K is equal to

Grade:12th pass

1 Answers

Arun
25763 Points
3 years ago
consider LHS, 

[4 cos^2(9)-3][4 cos^2(27)-3] 

multiplying and dividing with cos9.cos27, 

we get, 

[4cos^3(9)-3cos9][4cos^3(27)-3cos27]/c... 

{but cos3A=4cos^3(A)-3cos(A)} 

==>cos27.cos81/cos9.cos27 

=cos81/cos9 

=sin9/cos9 

=tan9 
 
Hence k = 9°

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free